Home/Class 12/Chemistry/

Conisder the chemical reaction
$${N}_{{{2}}}{\left({g}\right)}+{3}{H}_{{{2}}}{\left({g}\right)}\rightarrow{2}{N}{H}_{{{3}}}{\left({g}\right)}$$
The rate of this reaction can be expressed in terms of time derivatives of the concentration of $${N}_{{{2}}}{\left({g}\right)},{H}_{{{2}}}{\left({g}\right)}$$, or $${N}{H}_{{{3}}}{\left({g}\right)}$$. Identify the correct relationship among the rate expresisons.
(A) $${R}{a}{t}{e}=-\frac{{{d}{\left[{N}_{{{2}}}\right]}}}{{\left.{d}{t}\right.}}=-\frac{{1}}{{3}}\frac{{{d}{\left[{H}_{{{2}}}\right]}}}{{\left.{d}{t}\right.}}=\frac{{1}}{{2}}\frac{{{d}{\left[{N}{H}_{{{3}}}\right]}}}{{\left.{d}{t}\right.}}$$
(B) $${R}{a}{t}{e}=-\frac{{{d}{\left[{N}_{{{2}}}\right]}}}{{\left.{d}{t}\right.}}=-{3}\frac{{{d}{\left[{H}_{{{2}}}\right]}}}{{\left.{d}{t}\right.}}={2}\frac{{{d}{\left[{N}{H}_{{{3}}}\right]}}}{{\left.{d}{t}\right.}}$$
(C) $${R}{a}{t}{e}=-\frac{{{d}{\left[{N}_{{{2}}}\right]}}}{{\left.{d}{t}\right.}}=\frac{{1}}{{3}}\frac{{{d}{\left[{H}_{{{2}}}\right]}}}{{\left.{d}{t}\right.}}=\frac{{1}}{{2}}\frac{{{d}{\left[{N}{H}_{{{3}}}\right]}}}{{\left.{d}{t}\right.}}$$
(D) $${R}{a}{t}{e}=-\frac{{{d}{\left[{N}_{{{2}}}\right]}}}{{\left.{d}{t}\right.}}=-\frac{{{d}{\left[{H}_{{{2}}}\right]}}}{{\left.{d}{t}\right.}}=\frac{{{d}{\left[{N}{H}_{{{3}}}\right]}}}{{\left.{d}{t}\right.}}$$
Speed
00:00
07:32

## QuestionChemistryClass 12

Conisder the chemical reaction
$${N}_{{{2}}}{\left({g}\right)}+{3}{H}_{{{2}}}{\left({g}\right)}\rightarrow{2}{N}{H}_{{{3}}}{\left({g}\right)}$$
The rate of this reaction can be expressed in terms of time derivatives of the concentration of $${N}_{{{2}}}{\left({g}\right)},{H}_{{{2}}}{\left({g}\right)}$$, or $${N}{H}_{{{3}}}{\left({g}\right)}$$. Identify the correct relationship among the rate expresisons.
(A) $${R}{a}{t}{e}=-\frac{{{d}{\left[{N}_{{{2}}}\right]}}}{{\left.{d}{t}\right.}}=-\frac{{1}}{{3}}\frac{{{d}{\left[{H}_{{{2}}}\right]}}}{{\left.{d}{t}\right.}}=\frac{{1}}{{2}}\frac{{{d}{\left[{N}{H}_{{{3}}}\right]}}}{{\left.{d}{t}\right.}}$$
(B) $${R}{a}{t}{e}=-\frac{{{d}{\left[{N}_{{{2}}}\right]}}}{{\left.{d}{t}\right.}}=-{3}\frac{{{d}{\left[{H}_{{{2}}}\right]}}}{{\left.{d}{t}\right.}}={2}\frac{{{d}{\left[{N}{H}_{{{3}}}\right]}}}{{\left.{d}{t}\right.}}$$
(C) $${R}{a}{t}{e}=-\frac{{{d}{\left[{N}_{{{2}}}\right]}}}{{\left.{d}{t}\right.}}=\frac{{1}}{{3}}\frac{{{d}{\left[{H}_{{{2}}}\right]}}}{{\left.{d}{t}\right.}}=\frac{{1}}{{2}}\frac{{{d}{\left[{N}{H}_{{{3}}}\right]}}}{{\left.{d}{t}\right.}}$$
(D) $${R}{a}{t}{e}=-\frac{{{d}{\left[{N}_{{{2}}}\right]}}}{{\left.{d}{t}\right.}}=-\frac{{{d}{\left[{H}_{{{2}}}\right]}}}{{\left.{d}{t}\right.}}=\frac{{{d}{\left[{N}{H}_{{{3}}}\right]}}}{{\left.{d}{t}\right.}}$$

4.6
4.6
Correct9
Incorrect0
Still Have Question?